The impact of leadership behavior styles on employee performance: A field study of a sample of assistant deans and heads of scientific departments in the colleges of the University of Karbala - fahim aziz (Iraqi Journal for Administrative Sciences, 2024)
Due to the differing behaviors pursued by the leaders with the employees the subject of leadership styles requires study and examination continuously to determine the leadership style most appropriate to improve the performance of staff and the problem of this study was that (are you interested in administrative leaders the subject of study by pursuing the type of leadership which affects the performance of workers ).while the importance of the study originated as an important topic dealt with administrative work in the middle of changes and disturbances that took place in the Iraqi environment . The study deal with two variables and this and this variables are leadership styles and performance of staff in order to know the nature of the prevailing leadership styles and their compatibility with current trends and effect relationship on the performance of staff and study sample consisted of (40) of the associate deans and heads of scientific departments in five collages and the university of karbala and have been of the most important conclusion ( that there is a desire and inclination to adopt the lead in a community study of the pattern of the leading Democrats) and the most important recommendations ( is to promote self-confidence and leadership among workers and statement of their role to assume greater responsibilities through assign them and encourage them and give them authority in their field ).